2018
DOI: 10.3389/fnins.2018.00150
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Sharing Between Viruses and DLX Proteins: A Potential Cross-Reactivity Pathway to Neuropsychiatric Disorders

Abstract: The present study seeks to determine potential associations between viral infections and neuropsychiatric diseases. To address this issue, we investigated the peptide commonalities between viruses that have been related to psychiatric and neurological disorders—such as rubella, human immunodeficiency virus, and herpesviruses—and human distal-less homeobox (DLX) proteins expressed in developing brain—namely, DLX1, DLX2, DLX5, and DLX6. Peptide matching analyses revealed a high degree of pentapeptide sharing. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…Pentapeptide similarity between the NMDA 2A receptor and viral proteins have been previously reported [96]. Using the same mechanism, other peptide commonalities with high degree of pentapeptide sharing were found between viral peptides and the human distal-less homeobox (DLX) transcription factors expressed during early fetal neurodevelopment (DLX1, DLX2, DLX5, and DLX6) [94]. Analysis of the brain-specific DLX self-antigens pentapeptide revealed matching with several viruses that have been related to neurological disorders including rubella and herpesviruses [94].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 73%
See 2 more Smart Citations
“…Pentapeptide similarity between the NMDA 2A receptor and viral proteins have been previously reported [96]. Using the same mechanism, other peptide commonalities with high degree of pentapeptide sharing were found between viral peptides and the human distal-less homeobox (DLX) transcription factors expressed during early fetal neurodevelopment (DLX1, DLX2, DLX5, and DLX6) [94]. Analysis of the brain-specific DLX self-antigens pentapeptide revealed matching with several viruses that have been related to neurological disorders including rubella and herpesviruses [94].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 73%
“…Several recent studies aimed to explain the contribution of viral infections in CNS disorders. It was suggested that antiviral immune response cross-react with human NMDA receptors (2A subunit) [94], which are responsible for excitatory glutamatergic transmission and are ion channel proteins found in nerve cells [95]. Pentapeptide similarity between the NMDA 2A receptor and viral proteins have been previously reported [96].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins were examined in the present study in light of their involvement with neuronal migration, while it is highly likely that any alteration of their function or structure may affect higher cognitive processes through impairment of different mechanisms above and beyond migration (i.e., axon guidance, neurotransmission, excitatory-inhibitory balance, oscillatory neuronal firing, and others). Notably, these mechanisms can also be directly affected by cross-reactive targeting of proteins allowing membrane excitability (26)(27)(28)(29)(30), in a complex endotypical scenario that mirrors the phenotypical complexity of mental disorders without the need for a biunivocal match between them.…”
Section: The Brain Calcium Channel III or Voltage-dependent N-typementioning
confidence: 99%
“…Therefore, we here tried to elucidate the associations between HCMV infection, aberrant neuronal migration, and psychosis, building on previous research that had assessed peptide commonality and potential immune cross-reactivity between microbial and human proteins (26)(27)(28)(29)(30)(31). More specifically, we investigated the peptide platform shared by HCMV and human proteins involved in neuronal migration.…”
Section: Introductionmentioning
confidence: 99%